Quality assessment of rooftop runoff and harvested rainwater from a building catchment - Lee, J Y (Water science and technology : a journal of the International Association on Water Pollution Research, 2011)
A major obstacle to the promotion of rainwater harvesting is chemical and microbiological concerns. To determine its suitability as an alternative water resource, water quality parameters such as pH, turbidity and metal ion concentrations and counted total coliform, Escherichia coli and heterotrophic bacteria were measured. It was observed that the stored rainwater had a neutral average pH and that its turbidity depended on the duration and intensity of the rainfall event. Metal concentrations were within the permissible limits specified in the Korea drinking water standard. In addition, counts of coliform, E. coli and heterotrophic bacteria were higher in the first flush 5 min after the start of the rainfall event. Principal component analysis and correlation analysis through 40 events in 2009 showed that the quality of stored rainwater depends on the conditions of the catchment and storage tank and the antecedent dry period